Foreign influence and domestic policy: a survey - Toke Aidt; Facundo Albornoz; Esther Hauk (Center for Economic Studies and ifo Institute (CESifo), 2019)
In an interconnected world, economic and political interests inevitably reach beyond national borders. Since policy choices generate external economic and political costs, foreign state and non-state actors have an interest in inflencing policy actions in other sovereign countries to their advantage. Foreign influence is a strategic choice aimed at internalizing these externalities and takes many forms. We distinguish three broad types of intervention strategies, (i) voluntary agreement interventions between the intervening foreign power and the target country, (ii) policy interventions based on rewarding or sanctioning the target country to obtain a specific change in policy and (iii) institution interventions aimed at influencing the policy choice by changing the political institutions in the target country (with or without a civil war). We propose a unifying theoretical framework to understand when and which form of foreign influence is chosen and use it to organize and evaluate the new political economics literature on foreign influence along with work in cognate disciplines. Foreign intervention plays a more important role for a proper understanding of domestic policy choices, for institutional dynamics and for internal conflict than is commonly acknowledged in both empirical and theoretical research.
Keywords: D70; D72; D74; F13; F23; F51; F53; 330; foreign influence; international agreements; institutions; aid; sanctions; conflict